(untitled) - Brown, James Dean (Cambridge, UK, 2001)
This book presents a comprehensive, but practical, overview of the different phases and activities involved in the development and implementation of effective survey projects by language-teaching professionals. The text, which includes chapters on planning, designing, gathering, analyzing, and reporting survey research, would be accessible to graduate students, language teachers, administrators, and researchers. The theoretical and practical issues involved in survey design are defined and discussed in digestible chunks. All concepts are explained in an easy-to-follow, step-by-step manner, with ample examples and checklists provided. Each chapter also includes a list of key terms, a set of review questions, and a collection of exercises for practical application. In this text, language-teaching professionals will find all of the crucial information needed to survey students and teachers about their beliefs and practices. The results can then be used for developing curriculum, evaluating the success of language programs, or doing other relevant research.
Keywords: Language surveys